Handbook of Consumer Finance Research - Xiao, Jing Jian (Springer, 2016)
The fi rst edition of the book was published in 2008, during which American consumers were experiencing the great recession (2007–2009). After 6 years, the American economy is still recovering, and consumers are facing similar fi nancial challenges, inadequate savings for long-term goals such as retirement, and lack of control of various types of debts such as mortgages, credit cards, and education loans. More research is needed to better understand consumer fi nancial behaviors and provide professional assistance to economically vulnerable consumers. During the past decade, in the USA and other countries, the social movement of promoting consumer fi nancial literacy is gradually transferring to promoting consumer fi nancial capability. Financial capability implies that consumers need to possess adequate fi nancial knowledge and perform desirable fi nancial behaviors to maintain and improve their fi nancial well-being. In recent years, the research literature on consumer fi nance has increased greatly because of these social trends. For this reason, this new edition attempts to update research fi ndings and provide newly synthesized information for consumer fi nance researchers and practitioners who help consumers better manage their fi nances and enhance their fi nancial wellbeing. This book will enrich the literature of economics, fi nance, business, consumer science, family studies, human development, and related fi elds.